2019
DOI: 10.1080/21645515.2019.1667202
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of a quadrivalent inactivated influenza vaccine in pregnant women: a randomized, observer-blind trial

Abstract: Vaccination against influenza during pregnancy provides direct protection to pregnant women and indirect protection to their infants. Trivalent inactivated influenza vaccines (IIV3s) are safe and effective during pregnancy, but quadrivalent inactivated influenza vaccines (IIV4s) have not been evaluated in pregnant women and their infants. Here, we report the results of a randomized phase IV study to evaluate the immunogenicity and safety of IIV4 vs. IIV3 in pregnant women. Participants aged ≥18 years at weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…There is an extensive body of evidence in the literature from both HICs and LMICs that confirm the safety of maternal influenza vaccination (124)(125)(126)(127)(128)(129) [reviewed in (130)]. During the H1N1 influenza pandemic, data from Sweden and Argentina found that both AS03-adjuvanted and MF59-adjuvanted -H1N1 influenza vaccines were not associated with increased risk for low-birth weight or preterm birth or low Apgar score (131,132).…”
Section: Safetymentioning
confidence: 99%
“…There is an extensive body of evidence in the literature from both HICs and LMICs that confirm the safety of maternal influenza vaccination (124)(125)(126)(127)(128)(129) [reviewed in (130)]. During the H1N1 influenza pandemic, data from Sweden and Argentina found that both AS03-adjuvanted and MF59-adjuvanted -H1N1 influenza vaccines were not associated with increased risk for low-birth weight or preterm birth or low Apgar score (131,132).…”
Section: Safetymentioning
confidence: 99%
“…Furthermore, in vitro experiment, from multi European research collaboration, confirmed that quadrivalent inactivated influenza vaccine induces trained immunity responses against SARS-CoV-2 that enhance the COVID-19 protection[22]. Many previous studies demonstrated this vaccination benefice for pregnant women, and their newborns protected against influenza via passively acquired antibodies[23]. The quadrivalent vaccine immunogenicity and safety were confirmed for children aged 6-35 months and in older subjects aged 66-80 years[24].…”
Section: Resultsmentioning
confidence: 99%
“…If negative, another immediate RT-qPCR will be done from nasopharynx specimen If the viral load percentage is estimated clinically (low) between 32% and 05% just one RT-qPCR from the Nasopharynx should be done. 1 st Cq between [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] then control test Cq stays between [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] (one week after) 1 st Cq between [16][17][18][19][20][21][22][23][24][25][26][27][28]…”
Section: Clinical Interpretation Of the Expected Percentage Of The VImentioning
confidence: 99%
“…24 Recent studies with quadrivalent vaccines have shown vaccine effectiveness in pregnant women as well as the benefits for children. 25 This has allowed some vaccines to have, among their indications, the protection of pregnant women as well as children under 6 months of age by the transfer of antibodies from the mother to the child both during pregnancy and during lactation; i.e., passive protection of the infant from birth to 6 months of age after vaccination of the pregnant woman. 26 Other novel approaches, such as assessing both the safety of the seasonal influenza vaccine administered earlier in life, 3-4 months earlier than the current recommendation, especially in preterm infants that are at increased risk for influenza associated complications, and the impact of maternal antibodies on influenza vaccine responses are also being explored.…”
Section: Discussionmentioning
confidence: 99%